Problématique Maraîchère Induite Par La Nouvelle Dynamique Foncière Autour Des Bas-Fonds Urbains À Bouaké (Côte D’ivoire) - Kra Kouakou Valentin (European Scientific Journal, ESJ, 2018)
Urban agriculture in Côte d’Ivoire is an important activity in terms of food security, employment and response to environment. However in Bouaké, this agriculture and mainly gardening faces to a new land dynamics around intra-urban shallow. This situation results to emergence of new actors because of new stakes that represent shallows. As consequences we have a reduction of cultivated areas, an instability and a casualization of this type of agriculture. By analysis, it appears that of this sallow’s upgrading leads a redefinition of operating rules of flooded fields, witch were dropped to gardeners. More, this public servitudes and unbuilt areas subject to illegal land commercial transaction and anarchic buildings. We deduce a modification of these spaces operating rules, problems of land government and a neglect of urban agriculture in public politics and city management in Côte d’Ivoire.